Developing a Digital Accounting Management Module to Enhance the Operational Capabilities and Effectiveness of Village Fund Groups in Chiang Rai Province - Kasorn, Kasama; Sriwichai, Pheerapol (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Digital accounting management is a system for storing and processing information to facilitate operations suitable for the tasks or missions of village fund groups. This study has an important objective to develop a digital accounting management module to enhance the operational capabilities and effectiveness of the village fund in Chiang Rai province. Data collection was conducted through document analysis, system training, and questionnaire surveys with key informants, including staff and members of three village fund groups, totaling 150 people. The study results on the digital accounting management module consist of (1) use case diagram module, (2) activity diagram module, (3) sequence diagram module, and (4) class diagram module. Meanwhile, the module’s performance is enhanced in terms of program design, data storage, data retrieval, and data presentation at the highest level. The relationship between the digital accounting management module and operational capabilities and effectiveness is significant at a p-value of 0.01. Furthermore, the impact of digital accounting management is important in increasing convenience, accuracy, and transparency, ensuring accurate and up-to-date data recording, and instilling confidence in group members to enhance their ability to perform effectively.